Interpregnancy interval and prevalence of selected birth defects: A multistate study. Issue 2 (21st October 2021) - Liberman, Rebecca F.; Heinke, Dominique; Petersen, Julie M.; Parker, Samantha E.; Nestoridi, Eirini; Van Zutphen, Alissa R.; Nembhard, Wendy N.; Ramirez, Glenda M.; Ethen, Mary K.; Tran, Tri; Kirby, Russell S.; Getz, Kelly D.; et al.
Abstract: Background: Both short and long interpregnancy intervals (IPIs) have been associated with adverse birth outcomes. We undertook a multistate study to describe the prevalence of selected birth defects by IPI. Methods: We obtained data from nine population‐based state birth defects registries for singleton live births in 2000–2009 among mothers with a previous live birth identified through birth certificates. IPI was calculated as the difference between prior birthdate and start of the current pregnancy (conception date). We estimated prevalence of selected defects per 10, 000 live births and prevalence ratios (PRs) with 95% confidence intervals (CIs) overall and stratified by maternal age at previous birth and race/ethnicity. Primary analyses focused on short IPI < 6 months and long IPI ≥ 60 months compared to 18–23 months (referent). Sensitivity analyses limited to active‐surveillance states and those with<10% missing IPI. Results: Among 5, 147, 962 eligible births, 6.3% had short IPI while 19.8% had long IPI. Compared to referent, prevalence with short IPI was elevated for gastroschisis (3.7, CI: 3.0–4.5 vs. 2.0, CI: 1.6–2.4) and with both short and long IPI for tetralogy of Fallot (short: 3.4, 2.8–4.2 long: 3.8, 3.4–4.3 vs. 2.7, 2.3–3.2) and cleft lip ± palate (short: 9.9, 8.8–11.2 long: 9.2, 8.5–9.8 vs. 8.4, 7.6–9.2). Stratified analyses identified additional associations, including elevated prevalence of anencephaly with short IPI in younger mothers and limb defects with long IPI in those ages 25–34 at prior birth. Sensitivity analyses showed similar results. Conclusion: In this population‐based study, we observed increased prevalence of several birth defects with short and long IPI.